1994
DOI: 10.1111/j.1365-2141.1994.tb04793.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular defects in CRM+ factor VII deficiencies: modelling of missense mutations in the catalytic domain of FVII

Abstract: The molecular defects causing CRM+ factor VII deficiency were investigated in seven unrelated subjects and several members of their families. Four missense mutations located in the catalytic domain of factor VII were found. The previously reported 304Arg-->Gln substitution was present in the homozygous and heterozygous forms, with different polymorphic haplotypes, thus demonstrating that it is recurrent and frequent in the Italian population. The 310Cys-->Phe substitution was found in the homozygous form and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…They revealed the additional presence of FVII deficiency with plasma FVII:C levels of less than 1% and normal levels of FVII:Ag (Table I). FVII mutational analysis identified in both probands the presence, in the homozygote state, of the previously reported missense mutation Cys310Phe [6,7].…”
Section: Case Reportmentioning
confidence: 63%
“…They revealed the additional presence of FVII deficiency with plasma FVII:C levels of less than 1% and normal levels of FVII:Ag (Table I). FVII mutational analysis identified in both probands the presence, in the homozygote state, of the previously reported missense mutation Cys310Phe [6,7].…”
Section: Case Reportmentioning
confidence: 63%
“…Six of these patients belonging to 5 different kindreds came from our personal files. The remaining 16 patients were obtained from the literature (tables 1, 2) [10,13,14,19,20,21,22,23,24,25]. …”
Section: Resultsmentioning
confidence: 99%
“…Bernardi et al [17] have previously reported a missense mutation (Cys310Phe) in two unrelated pedigrees. A disulfide bond formed by Cys310 and Cys329 is highly conserved in serine protease, although the composition of the loop residues is variable.…”
Section: Discussionmentioning
confidence: 99%